KAJIAN DESKRIPTIF PEMANFAATAN INTERNET OLEH MAHASISWA DI JURUSAN TEKNIK OTOMOTIF FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG PADA TAHUN 2012 - Dwi Sudarno Putra; M Nasir; Irma Yulia Basri (Teknik Elektro Politeknik Negeri Padang, 2013)
This research is aim to describe how student use the internet in campus Automotive Engineering Department Padang State University at 2012. Descriptive Research Method was used for this research. Questionnaire was made to obtain the data. Its Questions are about the knowledge of internet facilities and use of the Internet by college students on campus. Questionnaire distributed to 138 respondents. From questionnaire data founded that 84% respondents using campus wifi hotspot for more than two days a week. About 99% of them use the internet to seek learning material to improve academic and technical knowledge. But, unfortunately Academic Information System are still not fully utilized. For example, only 9 of the respondents who have used discussion / chat online as one of a services of Academic Information System